Sesame Production and Export Performance in Sudan: A Comparative Advantage Analysis (University of Khartoum Journal of Agricultural Sciences, 2025)
The objective of this study was to determine the performanceof sesame production and export in Sudan during 1990-2005. Differentindicators, like instability index, comparative production performancecoefficient and revealed comparative advantage index, were used. Theresults showed that Sudan is one of the largest world producers andexporters of sesame, and has strong comparative advantage, but it has thehighest fluctuations compared to other sesame world suppliers. Thesefluctuations are due to constraints facing sesame production and exportlike domestic taxation, poor marketing services, lack of finance and poorquality standards. The paper concludes that the government policiesshould encourage sesame production and export in order to exploit Sudancomparative advantage in this product, and to benefit from theimprovement in the international market access to enter new markets.